2007
DOI: 10.1016/j.dsr.2007.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Ferromanganese nodule fauna in the Tropical North Pacific Ocean: Species richness, faunal cover and spatial distribution

Abstract: The poorly known ferromanganese nodule fauna is a widespread hard substratum community in the deep sea that will be considerably impacted by large-scale nodule mining operations. The objective of this study was to analyze the spatial distribution of the fauna attached to nodules in the Clarion-Clipperton Fracture Zone at two scales; a regional scale that includes the east (14°N, 130°W) and the west (9°N, 150°W) zones and a local scale in which different geological facies (A, B, C and west) are recognizable. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 47 publications
(68 reference statements)
3
52
0
Order By: Relevance
“…sponges, actinids, stalked crinoids, octocorallians, sedentary polychaetes, antipatharids, and tunicates, that settle on the nodules. This key conclusion has been supported by Thiel et al (1993) and Veillette et al (2007b). In addition, it appears that the nature of the sediments may differ, with softer sediments being located outside of the nodule fields compared to within them.…”
Section: The Structure Of Faunal Communities In the Cczsupporting
confidence: 53%
“…sponges, actinids, stalked crinoids, octocorallians, sedentary polychaetes, antipatharids, and tunicates, that settle on the nodules. This key conclusion has been supported by Thiel et al (1993) and Veillette et al (2007b). In addition, it appears that the nature of the sediments may differ, with softer sediments being located outside of the nodule fields compared to within them.…”
Section: The Structure Of Faunal Communities In the Cczsupporting
confidence: 53%
“…The sparse data on the influence of chemical substrate composition on deep-sea fauna are inconclusive: while foraminifera are reported to settle at higher densities on cobalt-rich crust than on basalt substrate (Verlaan, 1992), no clear relationship between faunal and geochemical composition of polymetallic nodules was found by Veillette et al (2007). The paucity of biological information for cobalt-rich crusts, and the possibility that the chemical composition of the crusts influences the composition and abundance of faunal communities on seamounts, has been recognized as a major impediment in developing and examining options for seabed mining operations on cobalt-rich crusts (Koslow, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…xenophyophores, antipatharian corals, sponges), as well as several meiofaunal and microbial taxa found inside the sediment-filled nodule crevices ( Fig. 3; Thiel et al 1993;Veillette et al 2007;Vanreusel et al 2016). A recent study by Amon et al (2016b) suggested that more than half of megafaunal species in the CCZ depend on nodules as a hard substrate.…”
Section: Introductionmentioning
confidence: 99%